ART DECO STYLE’S FEATURES IN THE TEXTILE WORKS OF DESIGNERS SONIA DELAUNAY AND PAUL POIRET - Zarembo, Liene (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Art Deco is an artistic term that stands for an elegant eclectic design style dating back to the 1920s. Style has affected virtually all industries, including architecture, fine arts, applied arts, interior design, industrial design, fashion and jewellery, as well as painting, graphics and cinema. Art Deco architecture and arts expanded on other movements - Constructivism, Cubism, Modernism, Bauhaus, and Futurism. Principles of Constructivism and Cubism are also used in contemporary textile patchwork and quilt. The aim of the paper: exploration of the features of Art Deco style in the textile works of 20th century designers - Sonia Delaunay and Paul Poiret. The methods of the research: exploration of theoretical literature and Internet resources, the experience of reflection.The research emphasizes Sonja Delaunay’s particular importance of textile works in the development of contemporary quilt in the 21st century.